Zika Virus Infection Induces Acute Kidney Injury Through Activating NLRP3 Inflammasome Via Suppressing Bcl-2 - Liu, Ting; Tang, Lantian; Tang, Hui; Pu, Jieying; Gong, Sitang; Fang, Danyun; Zhang, Hui; Li, Yi-Ping; Zhu, Xun; Wang, Weidong; Wu, Minhao; Liao, Yuhui; et al. (Frontiers in Immunology, 2019)
Zika virus (ZIKV) is a newly emerging flavivirus that broadly exhibits in various bodily tissues and fluids, especially in the brain, and ZIKV infection often causes microcephaly. Previous studies have been reported that ZIKV can infect renal cells and can be detected in the urine samples of infected individuals. However, whether ZIKV infection causes renal diseases and its pathogenic mechanisms remains unknown. Here, we identified that ZIKV infection resulted in acute kidney injury (AKI) in both newborn and adult mouse models by increasing the levels of AKI-related biomarkers [e.g., serum creatinine (Scr), kidney injury molecular -1 (Kim-1) and neutrophil gelatinase-associated lipocalin (NGAL)]. ZIKV infection triggered the inflammatory response and renal cell injury by activating Nod-like receptor 3 (NLRP3) inflammasome and secreting interleukin-1β (IL-1β). IL-1β inhibited aquaporins expression and led to water re-absorption disorder. Furthermore, ZIKV infection induced a decreased expression of B-cell lymphoma-2 (Bcl-2) in the kidney. Overexpression of Bcl-2 attenuated ZIKV-induced NLRP3 inflammasome activation in renal cells and down-regulated PARP/caspase-3-mediated renal apoptosis. Overall, our findings demonstrated that ZIKV infection induced AKI by activating NLRP3 inflammasome and apoptosis through suppressing Bcl-2 expression, which provided potential therapeutic targets for ZIKV-associated renal diseases.